Student Centered Teaching and Learning - Kiyamiddinovna, Umarova Malika (International Journal on Human-Computing Studies, 2023)
Intensively developing integration processes, growth professional and academic exchanges, deepening of international cooperation stimulate the progressive development of foreign language education. Under these conditions, a foreign language acquires the status of an effective tool for the formation of the intellectual potential of society, which becomes at the present historical stage one of the main resources for the development of the new state. In this article, author will discuss about a teaching technique which is student centered way of learning and teaching students in English.